Evaluation of physical development and adrenarche level of puberty age boys in st. Petersburg - V. L. Gritsinskaya; S. M. Mamedova; I. L. Nikitina (Медицинский совет, 2018)
In order to assess the growth and development of schoolchildren living in a metropolis, 809 boys aged 12 to 15 years were examined in St. Petersburg. Characteristics of indicators of physical development are given according to the norms of «WHO Growth Reference 2007»; the level of puberty - with the help of a phenotypic evaluation according to the method of M.V. Maksimova. The high prevalence of overweight (13.3%) and obesity (12.5%) among schoolchildren was revealed. It is noted that the initiation of the boys’ puberty occurs at the earlier time compared with the data given in the literature.